From learning to labour to learning for precarity. Issue 2 (3rd May 2016) - Dovemark, Marianne; Beach, Dennis
Abstract : A demand on national economies in the 1970s was that they should begin to increase their labour market flexibility, which came to mean transferring risks and insecurity onto workers. Education was one way to prepare future workers for this new situation. The present article examines this preparation of learning for precarity some 40 years on. It is based on long-term ethnographic research in the Swedish upper-secondary school sector in particular kinds of educational programmes that have been devised and promoted as a means of integrating 'lost pupils' into either academic or vocational studies. The findings show this is not what is developing in practice in these programmes.